2011
DOI: 10.1007/s10811-011-9703-2
|View full text |Cite
|
Sign up to set email alerts
|

The antialgal activity of 40 medicinal plants against Microcystis aeruginosa

Abstract: In search of a botanical algicide, 40 traditional medicinal plants were screened for antialgal activity against the bloom-forming cyanobacterium Microcystis aeruginosa using coexistence culture system assay. The results of the coexistence assay showed that significant inhibition of the algae at 800 mg L −1 were observed for methanolic extracts of the root of Salvia miltiorrhiza (Radix Salviae Miltiorrhizae), rhizome of Acorus tatarinowii (Rhizoma Acori), rhizome of Polygonum cuspidatum (Rhizoma Polygoni), cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…The effect of S. miltiorrhiza root extract in our study was less than reported in the literature, where extract of 800 mg L −1 caused an inhibition of 95% [20]. This difference could be due to different extracting procedures: methanolic extracts that were reconstituted in DSMO [20], whereas in our study a water extract was used.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The effect of S. miltiorrhiza root extract in our study was less than reported in the literature, where extract of 800 mg L −1 caused an inhibition of 95% [20]. This difference could be due to different extracting procedures: methanolic extracts that were reconstituted in DSMO [20], whereas in our study a water extract was used.…”
Section: Discussioncontrasting
confidence: 74%
“…This difference could be due to different extracting procedures: methanolic extracts that were reconstituted in DSMO [20], whereas in our study a water extract was used. The EC 50 of the water extract in our study was above 640 mg L for methanol extracts [20].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations